A Saving Science : Capturing the Heavens in Carolingian Manuscripts - Ramírez-Weaver, Eric M., 1971- (Book collections on Project MUSE., 2017)
"Focusing on the Handbook of 809, explores how the liberal arts, and in particular astronomy, experienced a revival in the ninth-century court of Charlemagne. Documents the utility of the constellations for prelates who needed to fix the floating feast of Easter and reckon time"--Provided by publisher